2014
DOI: 10.1103/physrevc.90.054604
|View full text |Cite
|
Sign up to set email alerts
|

Pre-equilibrium mechanisms in theNb93(p,α)inclusive reaction at incident energies from 65 to 160 MeV

Abstract: The reaction mechanism of pre-equilibrium proton-induced α-particle emission from 93 Nb at an incident energy of 100 MeV was investigated with polarized projectiles. A formalism based on the statistical multistep direct emission model of Feshbach, Kerman and Koonin was found to give a reasonably good reproduction of cross section and analyzing power angular distributions at various emission energies. Existing experimental distributions for the same reaction at an incident energy of 65 MeV were also analyzed wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…In our most recent work [5] we confirmed that knockout dominates in the mechanism of 93 Nb(p,α) reaction at incident energies of 65 and 160 MeV. However, at an intermediate incident energy of 100 MeV pickup is the most important process.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…In our most recent work [5] we confirmed that knockout dominates in the mechanism of 93 Nb(p,α) reaction at incident energies of 65 and 160 MeV. However, at an intermediate incident energy of 100 MeV pickup is the most important process.…”
Section: Introductionsupporting
confidence: 62%
“…This behaviour was observed for the first time in Ref. [5], and it needs to be interpreted in terms of the respective dynamics of knockout and pickup.…”
Section: Typical Features Of Inclusive Reactionsmentioning
confidence: 99%
See 3 more Smart Citations